Clinical Diagnosis and Management of a Congenital Bilateral Wattle Cyst in a Kid - K, Gayathri; S, Anoop; Venugopal, Syam; Martin, K.D John (Indian Journal of Veterinary Sciences and Biotechnology, 2025)
Wattle cysts or tassel cysts are superficial swellings in goats, which normally appear apparently harmless to  the quality of life of the species. A case of congenital bilateral  wattle cyst in a kid with its clinical differential diagnosis,  therapeutic management and clinical significance has been  put on record in this communication.
Keywords: bilateral wattle cyst; congenital; goat kid